Quality Control Analysis to Minimize Defective Products Using the Failure Mode and Effects Analysis (FMEA) Method in the Karya Raharja Village-Owned Enterprise (BUMDES) Convection Business - Janwar Saputra; Farliana Sutartiah; Muhammad Ihsan (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
The convection business unit operated by BUMDes Karya Raharja, located in Galudra Village, Pondok Salam Subdistrict, Purwakarta Regency, continues to face a high defect rate, averaging 15.52% per month, due to limited resources, the absence of standard operating procedures (SOPs), and a quality control system that has not been implemented optimally. This study aims to identify the failure modes occurring in the convection production process, assess their risk levels using the Failure Mode and Effect Analysis (FMEA) method, and formulate improvement proposals to reduce the defect rate. A descriptive case-study approach with a mixed-method design was employed, combining quantitative data on production and defect volumes with qualitative data obtained through observation and interviews across four production stages: cutting, sewing, finishing, and packing. Process FMEA (PFMEA) was applied to calculate the Risk Priority Number (RPN) for each failure mode, followed by the development of corrective actions using the 5W+1H approach. The results identified six failure modes with RPN values ranging from 108 to 280. Four failure modes were categorized as high priority (RPN ≥ 200): defective/stained fabric passing through to the finishing stage (RPN 280), loose or broken sewing thread (RPN 256), untidy stitching (RPN 252), and cut-fabric dimensions not matching the pattern (RPN 210). The sewing and finishing stages were identified as the critical points in the production process. The resulting improvement proposals are practical and do not require significant investment or complex systems. This study demonstrates that FMEA can be effectively applied in a resource-limited, village-owned enterprise (BUMDes) convection business.